Evaluation of grain size and content of nonplastic fines on undrained behavior of sandy soils. Issue 10 (3rd October 2021) - Xu, Ling-Yu; Cai, Fei; Zhang, Jing-Zhe; Pan, Dong-Dong; Wu, Qi; Chen, Guo-Xing
Abstract: Marine sandy soils may liquefy under wave loading and/or seismic loading. Current research shows that the presence of fines can significantly affect the liquefaction potential of sandy soils. Thus, a quantitative evaluation of the effect of fines on the undrained behavior of sandy soils can provide useful information on soil liquefaction that can advance the design of foundations of coastal structures. However, little is known about how the grain size of nonplastic fines affects the mechanical behavior of sandy soils. In this study, a series of strain-controlled monotonic undrained triaxial compression tests and critical-state constitutive modeling are carried out on a medium dense saturated sandy soil for various fines contents ( FC s), mean grain sizes ( d 50 f s) of nonplastic fines, and initial effective confining pressures. The results show that the peak deviatoric stress decreases significantly with decreasing d 50 f, especially for high FC s. The equivalent granular state parameter ( ψ *) at the phase transformation can be used to characterize the effect of fines on the dilatancy of sandy soils in constitutive modeling. Additionally, the initial value of ψ *( ψ 0 * ) serves as physical index for characterizing the influence of fines on the undrained instability state of sandy soils.